Combination of calretinin, MALAT1, and GAS5 as a potential prognostic biomarker to predict disease progression in surgically treated mesothelioma patients - Klotz, Laura Valentina; Casjens, Swaantje; Johnen, Georg; Taeger, Dirk; Brik, Alexander; Eichhorn, Florian; Förster, Laura; Kaiser, Nina; Muley, Thomas; Stolp, Christa; Schneider, Marc; Gleichenhagen, Jan; et al. (Lung cancer, 2024)
Background - The role of cytoreductive surgery for epithelioid pleural mesothelioma within a multimodal treatment approach remains controversial. Carefully selected patients benefit from cytoreductive surgery and adjuvant chemotherapy, but there is no established biomarker to predict tumor recurrence or progression during the course of the disease. The aim of this study was to identify potential biomarkers to predict therapeutic response in terms of progression-free survival. - Methods - Between 03/2014 and 08/2022, preoperative blood samples were collected from 76 patients with epithelioid pleural mesothelioma who underwent cytoreductive surgery as part of a multimodal treatment approach. Identification of potential biomarkers was performed by determination of mesothelin and calretinin, as well as specific long non-coding RNAs and microRNAs. Receiver operating characteristic analysis, Kaplan-Meier survival analysis, and Cox regression were used to assess the association between biomarker concentrations and patient recurrence status and survival. - Results - MALAT1, GAS5, and calretinin showed statistically significant increased biomarker levels in patients with recurrence in contrast to recurrence-free patients after surgical treatment (p < 0.0001, p = 0.0190, and p = 0.0068, respectively). The combination of the three biomarkers resulted in a sensitivity of 68 % and a specificity of 89 %. - Conclusion - MALAT1, GAS5, and calretinin could be potential biomarkers for the prediction of tumor recurrence, improving the benefit from multimodal treatment including cytoreductive surgery.
Online verfügbar: 24. April 2024, Artikelversion: 1. Mai 2024
Gesehen am 11.10.2024